Gap Junctions or Hemichannel-Dependent and Independent Roles of Connexins in Cataractogenesis and Lens Development - X. Jiang, J. (Current Molecular Medicine, 2010)
In the last decade or so, increasing evidences suggest that the mutations of two connexin genes, GJA3 and GJA8, are directly linked to human congenital cataracts in North and Central America, Europe and Asia. GIA3 and GIA8 genes encode gap junction-forming proteins, connexin (Cx) 46 and Cx50, respectively. These two connexins are predominantly expressed in lens fiber cells. Majority of identified mutations are missense, and the mutated sites are scattered across various domains of connexin molecules. Genetic deletion of either of these two genes leads to the development of cataracts; however, the types of cataracts developed are distinctive. More interestingly, microphthalmia is only developed in Cx50, but not Cx46 deficient mice, suggesting the unique role of Cx50 in lens cell growth and development. Knockin studies with the replacement of Cx46 or Cx50 at their respective gene locus further demonstrate the unique properties of these two connexins. Furthermore, the function of Cx50 in epithelial-fiber differentiation appears to be independent of its conventional role in forming gap junction junction channels. Due to their specific functions in maintaining lens clarity and development, and their malfunctions resulting in lens cataractogenesis and developmental impairment, connexin molecules could be developed as potential drug targets for therapeutic intervention for treatment of cataracts and other eye disorders. Recent advances in basic research of lens connexins and the discoveries of clinical disorders as a result of lens connexin dysfunctions are summarized and discussed here.
Keywords: phenotype